The Species Composition of Thrips (Insecta: Thysanoptera) Inhabiting Mango Orchards in Pulau Pinang, Malaysia - Hamaseh Aliakbarpour; Che Salmah Md. Rawi (Tropical Life Sciences Research, 2012)
A field study was conducted at two localities on Pulau Pinang, Malaysia, during two consecutive mango flowering seasons in 2009 to identify variations in the species composition of thrips infesting treated and untreated mango (Mangifera indica L.) orchards. The CO2 immobilisation technique and the cutting method were used to recover different thrips species from mango panicles and weed host plants, respectively. The mango panicles and various weed species within the treated orchard were found to harbour four thrips species from the family Thripidae. These species were identified as Thrips hawaiiensis (Morgan), Scirtothrips dorsalis (Hood), Frankliniella schultzei (Trybom) and Megalurothrips usitatus (Bagnall). The weed species Mimosa pudica, Cleome rutidosperma, Echinochloa colonum, Borreria laevicaulis, Veronia cinerea and Asystasia coromandeliana served as additional hosts to these thrips. Six thrips species were found in the untreated orchard. These species included Thrips palmi (Karny), Haplothrips sp. (Amyot and Serville) and the four thrips species found in the treated orchard. A brief description of the larvae for each genus is provided. Satu kajian lapangan telah dijalankan di dua tempat di Pulau Pinang, Malaysia semasa dua musim pembungaan mangga yang berturut-turut pada tahun 2009 untuk memastikan perubahan komposisi spesies thrips yang menyerang bunga mangga (Mangifera indica L.) di ladang yang dirawat dan tidak dirawat dengan racun serangga. Kaedah halang gerak CO2 dan pemotongan jambak bunga digunakan untuk mendapatkan spesies thrips yang berlainan dari jambak bunga mangga dan perumah rumpai masingmasing. Jambak bunga mangga dan pelbagai jenis spesies rumpai dalam dusun yang dirawat didiami oleh empat spesies thrips dari famili Thripidae; Thrips hawaiiensis (Morgan), Scirtothrips dorsalis (Hood), Frankliniella schultzei (Trybom) and Megalurothrips usitatus (Bagnall). Spesies rumpai, Mimosa pudica, Cleome rutidosperma, Echinochloa colonum, Borreria laevicaulis, Veronia cinerea dan Asystasia coromandeliana menjadi perumah tambahan kepada thrips ini. Enam spesies thrips ditemui di dusun yang tidak dirawat. Antaranya ialah Thrips palmi (Karny), Haplothrips sp. (Amyot and Serville) serta empat spesies yang ditemui di dusun yang dirawat. Huraian ringkas tentang larva untuk setiap genus disediakan.